Preliminary Assessment of Polysaccharide-Based Emulgels Containing Delta-Aminolevulinic Acid for Oral Lichen planus Treatment - Emilia Szymańska; Joanna Potaś; Mateusz Maciejczyk; Magdalena Ewa Sulewska; Małgorzata Pietruska; Anna Zalewska; Aleksandra Pietruska; Katarzyna Winnicka (MDPI AG, 2023)
Photodynamic therapy using delta-aminolevulinic acid is considered a promising option in the treatment of oral lichen planus. In the present work, three emulgel compositions prepared from natural polysaccharide gums, tragacanth, xanthan and gellan, were preliminarily tested for oromucosal delivery of delta-aminolevulinic acid. Apart from cytotoxicity studies in two gingival cell lines, the precise goal was to investigate whether the presence of the drug altered the rheological and mucoadhesive behavior of applied gelling agents and to examine how dilution with saliva fluid influenced the retention of the designed emulgels by oromucosal tissue. Ex vivo mucoadhesive studies revealed that a combination of xanthan and gellan gum enhanced carrier retention by buccal tissue even upon dilution with the saliva. In turn, the incorporation of delta-aminolevulinic acid favored interactions with mucosal tissue, particularly formulations comprised of tragacanth. The designed preparations had no significant impact on the cell viability after a 24 h incubation in the tested concentration range. Cytotoxicity studies demonstrated that tragacanth-based and gellan/xanthan-based emulgels might exert a protective effect on the metabolic activity of human gingival fibroblasts and keratinocytes. Overall, the presented data show the potential of designed emulgels as oromucosal platforms for delta-aminolevulinic acid delivery.